Women Detectives in Detective Fiction: A Formula Analysis on Dublin Murder Squad Series - Alya Khoirunnisa Fadhila; Ida Rochani Adi (Lexicon, 2021)
This paper studies the formulation of two women detectives in Tana French’s work, Cassie Maddox and Antoinette Conway, in the Dublin Murder Squad Series by exploring the hard-boiled fiction conventions which underlie the formulation of Tana French’s two female detectives. The objective of this study is to determine how French innovates the hard-boiled fiction conventions in the formation of her women detective characters, Cassie Maddox and Antoinette Conway. By employing formula analysis as theorized by John G. Cawelti (1976), the results of this study show that French innovates the hard-boiled formula in four aspects. First, French innovates the hard-boiled formula by expanding the concept of marginality from economic class to gender and race. The second innovation is the substitution of the hard-boiled convention which emphasizes on masculine toughness with resistance to patriarchal control. Third, French re-established the relationship between the detective and the character femme fatale. Their similarity of female experiences and perspective with the femme fatale makes these women detectives not only reveal the femme fatale as a murderer, but also the motives and scenarios behind their acts. Finally, French also innovates the antithetical nature of the hard-boiled detective’s presentation by offering a ‘feminine’ path to justice. These observations show that French’s innovations on hard-boiled conventions on her women detectives are the extensions of the women investigators in the antecedent feminist revisions of the hard-boiled stories which are heavily influenced by the second-wave feminist values. However, Tana French also inserts her own commentary on the new variants of female character shaped by the new post-feminist discourse which separates her women detectives from those in the antecedent feminist hard-boiled revision series.